DIGITALIZATION OF THE WORKPLACE AS A MEANS OF HR-BRANDING - ASTAFIEVA, Kateryna; BONDARCHUK, Olga; ASTAFIEV, Oleksandr; NIKULNIKOVA, Hanna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article indicates the relevance of the digitalization of the workplace as a means of HR-branding of the company. Researches of modern approaches to the interpretation of the term HR-branding have been carried out. It has been established that the latter should be understood as modern tools for the formation of a positive idea of the employer in the labor market. Taking into account the state of development of the scientific and technological process, namely, continuous digitalization, it is proposed to define the digitalization of the workplace as an HR-branding tool. It is proposed to understand the digitalization of the workplace as the process of introducing digital technologies and tools in the workplace to increase work efficiency, improve communications, automate routine tasks and improve the experience of employees. Workplace digitalization plays an important role in HR-branding as it helps companies attract and retain talented employees. Digital technologies make the workplace more attractive to potential candidates, providing a convenient and modern work experience. In addition, digital tools in HR-branding can be used to create branded content, training, employee motivation, online events, and more. All this helps companies to stand out in the labor market and attract the best specialists. The introduction of digitalization of the workplace will allow: to increase productivity and labor efficiency; improve communication and collaboration between colleagues and departments; optimization of business processes and automation of routine tasks; increasing labor flexibility and mobility; reduced paperwork and administrative costs; increasing the competitiveness of the business and the attractiveness for talented employees. All of the above will ensure the creation of a positive image of the employer in the labor market.